Retreatment of chemotherapy-resistant metastatic choriocarcinoma with immunotherapy - Adriana J. Wong; Lindsey Finch; Joseph Matt Pearson; Andre Pinto; Marilyn Huang (Gynecologic Oncology Reports, 2022)
Introduction: Recurrent metastatic choriocarcinoma is a rare disease with historically limited guidance in the literature regarding standardized treatment protocols. In this case report, we review the course of a patient with recurrent metastatic choriocarcinoma re-treated with single agent pembrolizumab.Our patient was initially diagnosed with metastatic choriocarcinoma (FIGO Stage IV, WHO Score 13) after presenting for evaluation of amenorrhea. She received standard treatment with etoposide, methotrexate, actinomycin D, cyclophosphamide and vincristine (EMA-CO), with a complete response. However, she recurred one year later. Molecular profiling of a chest wall tumor demonstrated strong expression of programmed cell death ligand 1 (PD-L1), and she was started on treatment with single agent pembrolizumab achieving a complete response. Unfortunately, she recurred again 6 months following completion of treatment. She was re-treated with pembrolizumab for 2 years with complete response after 25 cycles and is currently without evidence of disease. She has been followed on surveillance, with no evidence of disease for more than 24 months following treatment. Conclusion: This case represents the first to our knowledge to discuss re-treatment with pembrolizumab for relapsed choriocarcinoma after achieving a complete response.